Enabling Global Reach And Discoverability Of African Research Data - Cotera, Maria; Hahnel, Mark (My University, 2024)
Enabling global reach and discoverability of African research data - AfricArXiv Open Science Webinar Series 2024
Keywords: African research data; Data repositories; open science